2023
DOI: 10.1001/jama.2023.4902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Antibiotics on Mortality in Severe Alcohol-Related Hepatitis

Abstract: ImportanceThe benefits of prophylactic antibiotics for hospitalized patients with severe alcohol-related hepatitis are unclear.ObjectiveTo determine the efficacy of amoxicillin-clavulanate, compared with placebo, on mortality in patients hospitalized with severe alcohol-related hepatitis and treated with prednisolone.Design, Setting, and ParticipantsMulticenter, randomized, double-blind clinical trial among patients with biopsy-proven severe alcohol-related hepatitis (Maddrey function score ≥32 and Model for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Similarly, results from a study of protocolized use of amoxicillin-clavulanate in patients with severe alcohol-associated hepatitis did not show an increased incidence of C. difficile . 22 We did not observe any proven cases of CTX-resistant infection in this cohort. No fungal infections were observed in this study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Similarly, results from a study of protocolized use of amoxicillin-clavulanate in patients with severe alcohol-associated hepatitis did not show an increased incidence of C. difficile . 22 We did not observe any proven cases of CTX-resistant infection in this cohort. No fungal infections were observed in this study.…”
Section: Discussionmentioning
confidence: 50%
“… 20 , 21 Other sub-groups, however, have not demonstrated survival benefit with antibiotic prophylaxis, including those with severe acute alcohol-associated hepatitis and acute liver failure. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…A recently published multicenter, double-blind, randomized, placebocontrolled trial of Augmentin (amoxicillin/clavulanic acid) and prednisolone for 30 days in 280 patients with SAH did not show improvement of 2-month survival. 56…”
Section: Antibiotics In Alcohol-associated Hepatitismentioning
confidence: 99%
“…Initial studies on the empirical administration of amoxicillin/ clavulanic acid in addition to prednisolone therapy (the AntibioCor trial) showed a reduced cumulative incidence of infections (41.5% vs. 29.7%), while there was no beneficial effect on 2-month mortality. 67 Response to steroid treatment should be assessed by using the Lille score or by considering changes in bilirubin levels or the MELD score. 7,10 The Lille score is a dynamic score incorporating data from the beginning (day 1) and the course of steroid treatment (day 4 or day 7) to assess the response to steroid treatment, determine the risk of death, and evaluate the subsequent need for further steroid therapy.…”
Section: Glucocorticoid Treatmentmentioning
confidence: 99%